Lupinus angustifolius Protein Hydrolysates Reduce Abdominal Adiposity and Ameliorate Metabolic Associated Fatty Liver Disease (MAFLD) in Western Diet Fed-ApoE−/− Mice - Guillermo Santos-Sánchez; Ivan Cruz-Chamorro; Ana Isabel Álvarez-Ríos; José María Fernández-Santos; María Victoria Vázquez-Román; Beatriz Rodríguez-Ortiz; Nuria Álvarez-Sánchez; Ana Isabel Álvarez-López; María del Carmen Millán-Linares; Francisco Millán; Justo Pedroche; María Soledad Fernández-Pachón; et al. (MDPI AG, 2021)
Metabolic-associated fatty liver disease (MAFLD) is the most important cause of liver disease worldwide. It is characterized by the accumulation of fat in the liver and is closely associated with abdominal obesity. In addition, oxidative stress and inflammation are significant features involved in MAFLD. Recently, our group demonstrated that lupin protein hydrolysates (LPHs) had lipid lowering, antioxidant, and anti-inflammatory effects. Sixty male mice fed with a Western diet were intragastrically treated with LPHs (or vehicle) for 12 weeks. Liver and adipose tissue lipid accumulation and hepatic inflammatory and oxidant status were evaluated. A significant decrease in steatosis was observed in LPHs-treated mice, which presented a decreased gene expression of CD36 and LDL-R, crucial markers in MAFLD. In addition, LPHs increased the hepatic total antioxidant capacity and reduced the hepatic inflammatory status. Moreover, LPHs-treated mice showed a significant reduction in abdominal adiposity. This is the first study to show that the supplementation with LPHs markedly ameliorates the generation of the steatotic liver caused by the intake of a Western diet and reduces abdominal obesity in ApoE−/− mice. Future clinical trials should shed light on the effects of LPHs on MAFLD.